Diagnostic role of liquid-based cytology of bronchial lavage fluid in addition to bronchial brushing specimens in lung cancer. Issue 4 (August 2021) - Cao, Chao; Yu, Xuechan; Zhu, Tingting; Jiang, Qingwen; Li, Yiting; Li, Xinjian
Background: Liquid-based cytology (LBC) tests, including the liquid-based thin layer method, have demonstrated the highest potential for reducing false-negatives and improving sample quality. Method: This study aimed to evaluate the diagnostic role of LBC of bronchial brushing specimens in lung cancer. A total of 249 patients were analyzed in our study, involving 155 patients with combined bronchial brushing and bronchoalveolar lavage (BAL) and 94 patients with BAL alone. Results: The sensitivity in the combined bronchial brushing and BAL group was 61.4% in the diagnosis of lung cancer, which is much higher than with BAL alone. Rates of positive predictive values and negative predictive values in the combined group compared with the BALF alone group were 98.6% vs 100% and 47.6% vs 37.4%, respectively. Sensitivity in the BALF alone group was 12.5% in bronchoscopically invisible pulmonary lesions and as high as 52.1% in the combined group. Conclusion: The results from our study demonstrated that LBC of brushing samples could be used as an important complement of bronchoscopy and could have the potential to be widely applied.